2014
DOI: 10.1371/journal.pone.0102944
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel MSX1 Mutations Identified in Japanese Patients with Nonsyndromic Tooth Agenesis

Abstract: Since MSX1 and PAX9 are linked to the pathogenesis of nonsyndromic tooth agenesis, we performed detailed mutational analysis of these two genes sampled from Japanese patients. We identified two novel MSX1 variants with an amino acid substitution within the homeodomain; Thr174Ile (T174I) from a sporadic hypodontia case and Leu205Arg (L205R) from a familial oligodontia case. Both the Thr174 and Leu205 residues in the MSX1 homeodomain are highly conserved among different species. To define possible roles of mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 43 publications
0
11
0
2
Order By: Relevance
“…25 MSX1 and non-syndromic tooth agenesis Non-syndromic tooth agenesis (ns TA) is another common developmental anomaly that can be caused by MSX1 variants. 14 To date, nearly 20 MSX1 mutations have been related to ns TA 8,13,[26][27][28][29][30][31][32][33][34][35][36][37] (Table 2). Functional analyses of the mutant proteins suggest that haploinsufficiency of MSX1 underlies this phenotype.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 MSX1 and non-syndromic tooth agenesis Non-syndromic tooth agenesis (ns TA) is another common developmental anomaly that can be caused by MSX1 variants. 14 To date, nearly 20 MSX1 mutations have been related to ns TA 8,13,[26][27][28][29][30][31][32][33][34][35][36][37] (Table 2). Functional analyses of the mutant proteins suggest that haploinsufficiency of MSX1 underlies this phenotype.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
“…As a result, the function of MSX1 as a transcriptional repressor can be greatly impaired. 27,39,40 This could also be the result of epigenetic silencing of MSX1 by DNA methylation giving rise to either or combinations of its phenotypes or increase risk for tumoral growth Syndromes caused by MSX1 mutations Mutations in or including the MSX1 gene can also cause syndromic forms of tooth agenesis, including Wolf-Hirschhorn syndrome, Witkop syndrome, and tooth agenesis combined with orofacial clefting (Table 3). The Wolf-Hirschhorn syndrome is caused by a deletion of the WHS locus -including MSX1 -on chromosome 4p.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
“…It has been demonstrated that transcriptional repression by MSX1 occurs in the absence of DNA-binding sites; the repressor function is attributed to multiple domains in the N- and C-terminal regions of MSX136. In silico analysis studies have indicated that missense mutations affecting MH4 in MSX1 alter the encoded 3D structures of the proteins, specifically by destabilizing the helix-turn-helix motif or altering its protein-DNA interactions3738. Moreover in vitro studies have demonstrated that nuclear localization of MSX1 protein is mediated by the homeodomain37.…”
Section: Discussionmentioning
confidence: 99%
“…Традиционно считается, что аномалии зубов входят в состав генетической парадигмы, определяющей и развитие самой расщелины [17]. Действительно, доказано, что мутации генов MSX1 и PAX9, приводящие к селективной аплазии зубов [4,13,[18][19][20], также отвечают за развитие некоторых расщелин лица [11,15]. Кроме этих генов, однако, идентифицировано более 100, также сопряженных с РГН, но не влияющих на одонтогенез.…”
unclassified